Financial Management Analysis of Cafe Raihan in Mbarung Village, Babussalam District, Southeast Aceh Regency - Nasruddin, Nasruddin; Soefi, Roezaini; Malahayati, Rina (International Journal of Economics (IJEC), 2025)
This study aims to analyze the financial management practices applied at Cafe Raihan, a micro-enterprise in Mbarung Village, Babussalam District, Southeast Aceh Regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The results of the study indicate that financial management at Cafe Raihan is still done manually, inconsistently, and has not separated business and personal finances. Transaction recording is done simply and does not cover all aspects of business finances, while cash flow is uncontrolled due to the lack of planning and periodic reports. Cafe Raihan has also not utilized digital financial technology, and the owner's financial literacy is still limited. However, there is awareness and intention from the owner to improve financial management in the future. This study recommends the importance of financial literacy training, the use of digital recording applications, and ongoing assistance from the government or related institutions.